PEMBELAJARAN IPA SD BERORIENTASI DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN PROSES, AKTIVITAS DAN HASIL BELAJAR SISWA - Sutrisno Sutrisno (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
AbstractLearning in the realm of Unit Level Curriculum requires creativity of teachers in organizing learning activities. One form of creativity of the teacher is to organize learningdiscovery-oriented learning. This research aims to implement the elementary science teachingdevice discovery-oriented learning. Students are expected to bring the skills, learning activities,and create a learning atmosphere that is conducive for learning following the discovery-orientedlearning. This research is a class act consisting of two cycles. learning is done by using thesyllabus, lesson plan, teaching materials, worksheets, and tools discovery learning-orientedevaluation. During the study, carried out observation process skills, learning activities ofstudents and at the end of the study carried out tests to determine student learning outcomes.The results showed that the implementation of elementary science teaching discovery orientedlearning can help teachers to better learning. elementary science teaching discovery-orientedlearning can contribute to the learning outcomes, so that students can reach KKM of 91.2%.Activity of students in the learning quite varied, as appears 9 types of learning activities of students with great learning activity score was 94.85%. Process skills that can be exploredoptimally in elementary science teaching discovery-oriented learning is a skill to collect factsobservations, make a written report, and present the results of observations orally, with a scoreof 90.34% process skills.